Comparison of Parameter Estimation Methods to Determine the Frequency Data Magnitude of Aftershock in Nabire, Papua - Alvian M Sroyer; Tiku Tandiangnga; Felix Reba; Ishak Semuel Beno (Journal of Science and Science Education, 2018)
Many researchers use Weibull distribution to analyze wind speed data parameters and so forth, but in this research Weibull distribution is used to analyze the frequency data magnitude of aftershock. We use different methods for estimating Weibull distribution parameters. Some methods are compared according to the mean square error (MSE) criteria to select the best method. The parameter estimation results from the data are then used to determine the mean and magnitude of the earthquake. Further data is depicted in a curve for analysis. The case study in this study uses an aftershock frequency data in Nabire district, Papua. After the test of conformity with Kolmogorov-Smirnov test, it is obtained that the data follows the Weibull distribution pattern. Further research results show that the best method among the three methods is the maximum likelihood method (MLE). Keywords: Weibull, Maximum Likelihood Method (MLE), Least Squares Method (LSM), Graphical Method, Kolmogorov Smirnov, Magnitude